MBKM SANTRI PROGRAM; MANIFESTATION OF STUDENT CHARACTER FORMING IN PESANTREN - Afkarina, Izza; Rahman, Kholilur; BZ, Zakiyah (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2022)
This study aims to analyze and examine the implementation of MB-KM students in shaping the character of students with the status of students or Islamic tertiary institutions based on Islamic boarding schools, with the title "Student Exchange" program. This research uses qualitative research methods, the type uses case studies, focusing on implementing independent campus learning activities at Nurul Jadid University. This data collection technique uses interview techniques, observations, and field notes while implementing the Student Exchange program activities. The data source for this research is to conduct interviews with six informants consisting of; MB-KM students and hostel administrators. This study's results shape students' character through the MBKM Santri program by imitating religious values in their activities, from waking up until bedtime. In addition, it also improves interpersonal communication well when meeting new people. Even though they come from different college backgrounds, they are accustomed to being in harmony with each other and understanding one another. This research implies that students are motivated to dare to study outside other universities to increase their potential for hard and soft skills.